Laparoscopic retroperitoneal partial nephrectomy using an ergonomic chair: demonstration of technique and matched‐pair analysis - Rassweiler, Jens; Klein, Jan; Tschada, Alexandra; Gözen, Ali Serdar (BJU international, 2017)
Objectives To present the technique and long?term results of retroperitoneal laparoscopic partial nephrectomy (LPN), focusing on the impact of an ergonomic platform. Patients and Methods Between January 2000 and May 2016, 287 patients (193 men, 94 women) underwent LPN performed by four surgeons. The median (range) patient age was 59 (19?85) years, tumour size 3.1 (1?9) cm and PADUA score 7.3 (6?12). Access was retroperitoneal in 235 cases (82%). Since October 2010, we have used the ETHOS? chair (ETHOS?, Seattle, WA, USA) during excision of the tumour in 130 patients (45.3%). A total of 51 tumours (17.7%) were excised without ischaemia and 226 (78.7%) under warm ischaemia, with clamping of the renal artery using an enucleo?resection technique. We suture the resection bed and perform renorrhaphy using a barbed?suture pre?loaded with absorbable LAPRA?TY? clips (Ethicon, Somerville, NJ, USA). The impact of the ETHOS chair was examined using a matched?pair analysis (66 with ETHOS chair vs 67 without ETHOS chair). Results The median (range) operating time was 146 (60?325) min, the median (range) estimated blood loss was 99 (10?3 000) mL and the mean (range) warm ischaemia time (WIT) was 17.1 (7?47) min. Histology showed 240 (83.6%) renal cell carcinomas (RCCs) and 46 (15.9%) benign tumours. The cumulative overall disease?free survival rate after a median (range) follow?up of 84 (3?155) months was 100% for 203 pT1 RCCs and local recurrence was observed in one patient (0.4%), who was managed by radical nephrectomy. There were two conversions (0.7%) to open surgery, both to hand?assisted laparoscopy. Perirenal haematoma was observed in 13 patients (4.5%). A total of 20 patients (6.9%) required transfusions (2?11 units). We observed five urine leaks (1.7%) requiring prolonged drainage. The median (range) length of hospital stay was 5 (3?24) days. Three patients developed arteriovenous fistulas, which were successfully occluded by superselective embolization (1.0%). Use of the ETHOS chair resulted in shorter operating time (134.7 vs 168.5 min; P = 0.04), including WIT (13.1 vs 15.9 min; P = 0.01), and a lower complication rate (15 vs 29.8%; P = 0.02). Conclusions Laparoscopic partial nephrectomy is technically difficult but oncologically effective. Standardization and simplification of endoscopic suturing using the ETHOS chair significantly improved the outcomes of the surgical procedure.
First published: 12 August 2016
Gesehen am 04.04.2018